MEDIA PEMBELAJARAN BAHASA INGGRIS BERBASIS MULTIMEDIA MENGGUNAKAN APLIKASI ADOBE FLASH PADA SDN 58/X TELUK MAJELIS : Multimedia-based English learning media;Class VI. - Megawati, Merti; -, Nilawati (JURNAL AKADEMIKA, 2021)
This development research aims to develop interactive multimedia-based learning media for SDN 58 / X Learning about media experts, material experts and students.The method used in this research is research and development. This research was conducted at SDN 58 / X TelukMajelis.The research procedure carried out by researchers consists of 7 stages, namely the potential and problem stage, the stage of data collection, the product design stage, the product validation stage, the design revision stage, the product trial stage, and the product revision stage.The results of this study are interactive multimedia-based English learning media using Adobe Flash applications for grade VI English reading skills.The final results of the quality of this English learning media according to media experts 90% for the percentage of quality media with a very good category, and material experts rate 75% for the percentage of media quality with a good category, English teachers rate 95% for the percentage of media quality with the category of strongly agree , and finally the assessment of the students 85% for the percentage of media quality in the category of strongly agree.